Democracia, pluralismo y estructura del cuerpo docente en la Educación Jurídica Superior - Barreyro, María Emilia (2015)
Reflections that form this essay aim to lay out the necessity of moving the focus from the classroom situations to the structure of the teaching staff in law-teaching institutions, in order to achieve a better understanding of how this teaching ought to be. The general hypothesis throughout this work holds that pluralism in teaching staff has both epistemic and political value, taking the case of Facultad de Derecho Universidad de Buenos Aires as a model and trigger of some reflections about this matter.